Алельний стан гена Cre8 стійкості до нематоди Heterodera avenae Woll. у сортів пшениці м’якої української селекції - Карелов, А.В.; Козуб, Н.О.; Созінов, І.О.; Пилипенко, Л.А.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2016)
Aim. The work is devoted to discovering the presence of resistance to the cereal cyst nematode in the Ukrainian common
wheat germplasm. Methods. The molecular-genetic marker wri15 co-segregating with the Cre8 gene that confers moderate
resistance to H. avenae was used. Results. Common wheat cultivars developed in different climatic zones (24 in total)
were studied. Two cultivars, carrying the resistant allele of the marker were detected. Conclusions. In the Ukrainian
common wheat germplasm there are cultivars that can be the source of moderate resistance to the cereal cyst nematode.
They probably inherited the resistant allele of the gene from old German cultivars. It is reasonable to keep studying
Ukrainian common wheat germplasm to search for sources of resistance conferred by the Cre8 gene.
Keywords: cereal cyst nematode, common wheat, molecular markers, Cre8.